Language and Literacy Stimulation Model for Early Childhood Based on Interaction and The Learning Environment - Zahroh, Shofiyatuz; Nurmala, Dinda Permata; Nahdiyah, Naylatun (JOYCED: Journal of Early Childhood Education, 2026)
Purpose - Early childhood language and emergent literacy are often promoted through discrete activities or single instructional media, leaving limited evidence on how everyday classroom practices function as an integrated pedagogical system. This study examined language and literacy development practices at RA Nurul Ummah, Sidoarjo, Indonesia. It contributes a context-sensitive practical framework that connects social interaction, visual media, storytelling, and verbal routines rather than positioning one strategy as sufficient. Design/methods/approach - A descriptive qualitative design was employed. Data were generated through five classroom observations, semi-structured interviews, and instructional documents involving 72 children aged 3–6 years, six teachers, one principal, and eight parents. The data were analyzed using reflexive thematic analysis. Four interconnected patterns emerged: peer interaction expanded expressive language; visual media linked words to concrete meanings; interactive storytelling supported receptive and expressive language; and verbal instructions strengthened functional comprehension. Teacher questioning, vocabulary repetition, and emotionally safe dialogue enabled these practices to operate as a coherent learning environment. Findings - The findings indicate that language and literacy development was embedded in children’s daily participation rather than delivered as an isolated lesson. This study offers early childhood educators a practical basis for designing culturally responsive, interaction-rich language and literacy environments. Research implications/limitations – The findings offer practical guidance for creating culturally responsive and interaction-rich environments that support language and literacy development. However, as the study was conducted in a single kindergarten setting, further research across diverse institutions and participant groups is needed to confirm and extend these findings. Originality/value – This study extends understanding of language and literacy development by highlighting the role of culturally responsive daily participation in early childhood education.